The role and competence of agricultural development officers as community developers: a scoping review - Syarifuddin, Noviatin; Abu Samah, Asnarulkhadi; Burhan, Nik Ahmad Sufian; Arif Shah, Jasmin (Human Resource Management Academic Research Society, 2021)
Discussions on agricultural development officers in the field of social science studies have long been discoursed by academics, community development practitioners and various formal and informal agencies since 1960. However, the results of studies focusing on the role and competencies of development officers in the context of community development remain. limited. Accordingly, the study focuses on two main objectives, namely i) to analyse the trends of the study findings on the role and competencies in the field of community development and ii) to identify the role and competencies of agricultural development officers as community developers. The study analyses secondary data through content analysis techniques and examines the theme of the role and competencies of agricultural development officers in the context of community developers thematically. The results of the first objective study, found that the trend of research findings on the role and competence of agricultural development officers in the field of community development began to be analysed as a field of knowledge since 1960. While the analysis of the role and competencies of agricultural development officers has identified 11 themes as community developers: i) identify community forms and processes of social action; ii) respect the diversity/pluralism and multi-culture of community members; iii) implement development programs appropriate to the demographics of the community; iv) skilfully encourage community involvement in development programs; v) have information and ability to deliver developmental education; vi) establish interpersonal relationships; vii) have knowledge of organization; viii) leadership; ix) organizational management; x) have professionalism; and xi) master the field of community development in terms of theory and practice. In conclusion, the implications of the study on the literature highlights are able to build a deep and systematic understanding of the role and competencies of agricultural development officers in the context of community development practitioners in Malaysia.